Decentralized adaptive output tracking control of interconnected nonlinear systems with actuator failures - Wang, Wei (2013)
In this paper, a decentralized adaptive backstepping control scheme is proposed to achieve trajectory tracking for a class of nonlinear interconnected systems with stuck type actuator failures. To compensate for the effects of failed actuators, more unknown parameters in addition to original system parameters need to be identified. A damping term is introduced in constructing the stabilizing function in the first step of backstepping design procedure for robustness with respect to the nonlinear interactions between subsystems. It is shown that the global uniform boundedness of all closed-loop signals is ensured with the designed local adaptive controllers. Further, the overall tracking error converges to a residual set ultimately which can be made as small as desired by properly choosing the design parameters.